Internet Addiction, Smartphone Addiction, and Hikikomori Trait in Japanese Young Adult: Social Isolation and Social Network - Tateno, Masaru; Teo, Alan R.; Ukai, Wataru; Kanazawa, Junichiro; Katsuki, Ryoko; Kubo, Hiroaki; Kato, Takahiro A. (Frontiers in Psychiatry, 2019)
Background: As the number of internet users becomes higher, problems related to internet overuse are becoming more and more serious. Adolescents and youth may particularly be attracted to and preoccupied with various online activities. In this study, we investigated the relationship of internet addiction, smartphone addiction and the risk of hikikomori, severe social withdrawal, in Japanese young adult. Methods: The subjects were 478 college/university students in Japan. They were requested to complete the study questionnaire, which consisted of questions about demographics, internet use, the Internet Addiction Test (IAT), the Smartphone Addiction Scale (SAS)-Short Version (SV), and the 25-item Hikikomori Questionnaire (HQ-25), etc. We investigated the difference and correlation of the results between two groups based on the purpose of internet use or the total score of each self-rating scale, such as screened positive or negative for the risk of internet addiction, smartphone addiction or hikikomori. Results: There was a trend that males favored gaming in their internet use while females used the internet mainly for social networking via smartphone, and the mean SAS-SV score was higher in females. Two-group comparisons between gamers and social media users, according to the main purpose of internet use, showed that gamers used the internet longer and had significantly higher mean IAT and HQ-25 scores. Regarding hikikomori trait, the subjects at high risk for hikikomori on HQ-25, had longer internet usage time and higher scores on both IAT and SAS-SV. Correlation analyses revealed that HQ-25 and IAT scores had a relatively strong relation, although HQ-25 and SAS-SV had a moderately weak one. Discussion: Internet technology has changed our daily lives dramatically and altered the way we communicate as well. As social media applications are becoming more popular, users are connected more tightly to the internet and their time spent with others in the real world continues to decrease. Males often isolate themselves from the social community in order to engage in online gaming while females use the internet as to not be excluded from their communications online. Mental health providers should be aware of the seriousness of internet addictions and hikikomori.